Peningkatan Sistem Informasi Manajemen Dalam Meningkatkan Disiplin Kerja Dengan Kinerja Karyawan Pada RSUD Saiful Anwar - Pribawaningsih, Lia Pribawaningsih; Gladys Brinita Santi (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2021)
This study was conducted to determine the effect of human resource information systems, competency and discipline on employee performance. The object of research is one of the hospital in the city of Malang. Population used were all employees of the hospital. Quantitative research methods using Path Analysis. The results showed that there is significant influence of HR Information Systems, competence and Discipline Work on employee performance either partially or simultaneously. The survey results revealed that the simultaneous Effect of HR information systems, Competence, Work Discipline against employee performance in the category of very significantly by 75.5%. These results indicate that the effect of these three variables including very significant category while the remaining 24.5% is a variable that is not research as compensation, organizational culture, communication work.